2018
DOI: 10.1038/s41419-018-0811-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-inhibition of mTORC1, HDAC and ESR1α retards the growth of triple-negative breast cancer and suppresses cancer stem cells

Abstract: Triple-negative breast cancer (TNBC) is the most refractory subtype of breast cancer. It causes the majority of breast cancer-related deaths, which has been largely associated with the plasticity of tumor cells and persistence of cancer stem cells (CSCs). Conventional chemotherapeutics enrich CSCs and lead to drug resistance and disease relapse. Development of a strategy capable of inhibiting both bulk and CSC populations is an unmet medical need. Inhibitors against estrogen receptor 1, HDACs, or mTOR have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“… 59 , 60 However, the prognosis and clinical outcomes of TNBC, which does not express estrogen receptors (ER), progesterone receptors (PR) or HER2, are far from satisfying. 61 , 62 Although TNBC only accounts for a small portion (10%–20%) of all breast cancer cases, it has a high mortality risk and is more aggressive than other breast cancer sub-types. 63 Given the absence of definitive therapeutic targets (ER, PR or HER2), only a few adjuvant treatments, such as conventional surgery, chemotherapy and radiotherapy, can provide any benefit for TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 59 , 60 However, the prognosis and clinical outcomes of TNBC, which does not express estrogen receptors (ER), progesterone receptors (PR) or HER2, are far from satisfying. 61 , 62 Although TNBC only accounts for a small portion (10%–20%) of all breast cancer cases, it has a high mortality risk and is more aggressive than other breast cancer sub-types. 63 Given the absence of definitive therapeutic targets (ER, PR or HER2), only a few adjuvant treatments, such as conventional surgery, chemotherapy and radiotherapy, can provide any benefit for TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Formazan crystals were solubilised in dimethylsulfoxide (DMSO, Sigma Aldrich V R , St. Louis, MO), and absorbance rates were measured at 562 nm in ThermoPlate V R TP Reader. Chalcones 1,6,8,9,11,17,19, and 20 had the highest antiproliferative activity and were assayed against both cell lines at seven concentrations, ranging from 1.25 to 80 lM for IC 50 values determination.…”
Section: Antiproliferative Activity Of Chalcones 1-20mentioning
confidence: 99%
“…We assayed analogues substituted by nitro (2), trifluoromethyl (3), cyano (4), and halogens (5-12). 3-Chloro-4'-aminochalcone (9) and 2-fluoro-4'aminochalcone (11) were the two most active compounds against MCF-7 line, with %MVC rates of 52.5 ± 6.7 and 50.3 ± 7.8, respectively. 3-Fluoro-4'-aminochalcone (8) was the most potent against MDA-MB-231 line, with %MVC of 73.3 ± 5.4.…”
Section: Antiproliferative Activity Of Chalcones 1-20mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, one study has demonstrated that miR-128-3p inhibits the stemlike cell features of BCSCs via inhibition of the Wnt signaling pathway by downregulating NEK2, which provides a new target for breast cancer treatment [31]. Then, another study indicates that CD24 and CD44 are cancer stem cells which can promote the development of breast cancer [32]. Many miRNAs have been shown to regulate the self-renewal and differentiation of CSCs, such as the let-7 miRNA family [33,34].…”
Section: Discussionmentioning
confidence: 99%